2022
DOI: 10.3389/fpubh.2022.1052273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food safety supervision efficiency on preventing and controlling mass public crisis

Abstract: Food safety has received unprecedented attention since the COVID-19 outbreak. Exploring food safety regulatory mechanisms in the context of cluster public crises is critical for COVID-19 prevention and control. As a result, using data from a food safety regulation survey in the Bei-jing-Tianjin-Hebei urban cluster, this paper investigates the impact of food safety regulation on the prevention and control of COVID-19. The study found that food safety regulation and cluster public crisis prevention and control h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…However, some scholars have found that agricultural credit also can inhibit agricultural green production efficiency. Therefore, according to Ding et al (2022a), Ding et al (2022b), Wen and Wang (2022), this paper establishes a theoretical framework for the impact of agricultural credit on agricultural green production efficiency from both the driving and inhibiting effects. Figure 1 is the theoretical framework of this paper.…”
Section: Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, some scholars have found that agricultural credit also can inhibit agricultural green production efficiency. Therefore, according to Ding et al (2022a), Ding et al (2022b), Wen and Wang (2022), this paper establishes a theoretical framework for the impact of agricultural credit on agricultural green production efficiency from both the driving and inhibiting effects. Figure 1 is the theoretical framework of this paper.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…According to Ding et al (2022b) and Du et al (2022a), this paper uses the Metafrontier-Malmquist-Luenberger index (MML) based on DEA model to measure the agricultural green production efficiency (AGPE). Significant differences exist in regions' natural resource endowments and agricultural production technologies.…”
Section: Metafrontier-malmquist-luenberger Indexmentioning
confidence: 99%
“…Therefore, strengthening the information monitoring of sustained agricultural output and supply has become the top priority for ensuring food security. At present, digital technology has been widely used in storage, circulation supervision, big data, safety supervision, and other aspects (Ding et al, 2022;Hu et al, 2023a;Xi et al, 2021). Digital villages utilize the Internet, big data, and other modern information technologies to promote agricultural and rural development and improve rural production and living conditions.…”
Section: Introductionmentioning
confidence: 99%